2021
DOI: 10.1093/eurheartj/ehaa982
|View full text |Cite
|
Sign up to set email alerts
|

A leucopoietic-arterial axis underlying the link between ambient air pollution and cardiovascular disease in humans

Abstract: Aims  Air pollution [i.e. particulate matter with diameter <2.5 μm (PM2.5)] is a risk factor for major adverse cardiovascular events (MACE). While PM2.5 promotes leucopoiesis and atherosclerotic inflammation in experimental models, it is unknown whether this occurs in humans. We tested in humans (a) whether PM2.5 associates with higher leucopoietic tissue activity and arterial inflammation (ArtI), (ii) whether these associations persist after accounting for the effects of potential con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Four studies 83 , 84 , 86 , 87 adopted the WHO definition of osteopenia and/or osteoporosis to classify the subjects. 57 , 58 , 60 , 61 Besides, Alvær et al 81 defined subjects with Z-score ≤ −1 as having low BMD, which does not comply with the existing recommendation. Adjusted regression coefficient (β), 81 , 82 , 85 , 86 , 93 , 94 odd ratio (OR), 81 , 82 , 84 , 87 mean differences, 86 , 88 or Pearson correlation coefficient (r) 83 were used in these studies to demonstrate the association between PM and bone mass.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies 83 , 84 , 86 , 87 adopted the WHO definition of osteopenia and/or osteoporosis to classify the subjects. 57 , 58 , 60 , 61 Besides, Alvær et al 81 defined subjects with Z-score ≤ −1 as having low BMD, which does not comply with the existing recommendation. Adjusted regression coefficient (β), 81 , 82 , 85 , 86 , 93 , 94 odd ratio (OR), 81 , 82 , 84 , 87 mean differences, 86 , 88 or Pearson correlation coefficient (r) 83 were used in these studies to demonstrate the association between PM and bone mass.…”
Section: Resultsmentioning
confidence: 99%
“…To date, multiple causes are considered be associated with high dose or long‐term exposure to PM 2.5 ‐induced cardiac injury such as oxidative stress (Gangwar et al., 2020 ; Wang et al., 2018 ) and inflammation (Abohashem et al., 2021 ). Prolonged exposure to particulate pollution is identified to cause endothelial and systematic inflammation (Pope et al., 2016 ) and epigenetic changes (Madrigano et al., 2011 ), which may contribute to cardiac injury.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure studies in animals revealed that in the setting of atherosclerosis, plaque development was accelerated [104,105]. Body scans by positron emission tomography in men revealed that particulate matter induces coronary inflammation, which was associated with higher cardiovascular risk [106]. In further human studies, platelet hyperreactivity and thrombus formation were observed [107,108].…”
Section: Oxidative Stress and Inflammation By Air Pollutionmentioning
confidence: 97%